International Bribery: Policies, barriers and proposals - Gómez de la Torre, Ignacio Berdugo (2019)
The internationalization of the economy acts as a conditioner for international corruption. The first point analyzed is international bribery as a corrupt behavior carried out by companies, its negatives consequences on Human Rights and the problems of having an effective criminal policy against it. In this context, the US regulations, the OECD agreement and the problems and proposals for their application by States and companies are also analyzed.